الوقف والابتداء - Al-Samarqandi | السمرقندي, Muhammad bin Mahmoud bin Muhammad | محمد بن محمود بن محمد (King Abdulaziz Complex for Endowment Libraries | مجمع الملك عبدالعزيز للمكتبات الوقفية, 2023)
A good copy with comments, some of which indicate the end of the Qur’anic parties, and written in black and red ink, and it is incomplete from the end of it. | نسخة جيدة عليها تعليقات بعضها لبيان انتهاء الأحزاب القرآنية، ومكتوبة بمداد أسود وأحمر، وهي ناقصة من آخرها.